(untitled) (Scientific journal of the Fergana State University, 2023)
This article will discuss the shortcomings and problems that arise in the classroom, ways to eliminate them, the introduction of pedagogical technologies in the educational process, methods and means of using them to improve the effectiveness of teaching, problematic, modular, design and information technologies, the structure of modern learning, the methodology of practical implementation, the levels of knowledge acquisition by the audience in this process.